Intelligent distributed computing X : proceedings of the 10th International Symposium on Intelligent Distributed Computing -- IDC 2016, Paris, France, October 10-12 2016 - Badica, Costin; El Fallah Seghrouchni, Amal; Beynier, Aurélie; Camacho, David; Herpson, Cédric; Hindriks, Koen V.; Novais, Paulo (Springer, 2016)
This book presents the combined peer-reviewed proceedings of the tenth International Symposium on Intelligent Distributed Computing (IDC'2016), which was held in Paris, France from October 10th to 12th, 2016. The 23 contributions address a range of topics related to theory and application of intelligent distributed computing, including: Intelligent Distributed Agent-Based Systems, Ambient Intelligence and Social Networks, Computational Sustainability, Intelligent Distributed Knowledge Representation and Processing, Smart Networks, Networked Intelligence and Intelligent Distributed Applications, amongst others.
Includes author index.
Keywords: Artificial intelligence -- Congresses.; Electronic data processing -- Distributed processing -- Congresses.; elektronické knihy; electronic books